The Role Of Governance In Improving The Effectiveness Of Public Bureaucracy: A Systematic Review - Sony Garneta, Belva Fitriyah; Wulandari, Natasya Eka (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study discusses the role of governance in enhancing the effectiveness of public bureaucracy, focusing on the challenges faced and strategies that can be implemented. Through a systematic review, several key issues are identified, including a lack of transparency, accountability, and public participation that hinder bureaucratic performance. Theories of New Public Management (NPM), accountability, and public participation are used as frameworks to analyze the interactions between government, society, and managerial practices. The research findings indicate that the implementation of information technology and the Electronic Government System (SPBE) can improve efficiency and transparency in public services. Additionally, good accountability practices and active civil society involvement in oversight can build public trust in government. Development recommendations include enhancing transparency, strengthening public participation, investing in information technology, and reforming policies to create a more inclusive environment. This study emphasizes that the integration of efficiency, accountability, and public participation is key to creating quality public services and enhancing government legitimacy, which in turn supports sustainable development.